Cover Picture: Halogen‐Dependent Surface Confinement Governs Selective Alkane Functionalization to Olefins (Angew. Chem. Int. Ed. 18/2019). Issue 18 (1st March 2019) - Zichittella, Guido; Scharfe, Matthias; Puértolas, Begoña; Paunović, Vladimir; Hemberger, Patrick; Bodi, Andras; Szentmiklósi, László; López, Núria; Pérez‐Ramírez, Javier
Abstract : Heaven can wait . Operando spectroscopy techniques can distinguish surface and gas‐phase processes in alkane oxyhalogenation. In their Communication onpage 5877, J. Pérez‐Ramírez et al. unravel the mechanistic origin of the halogen effect steering catalysis. Selective alkane conversion into olefins is driven by surface‐confined chlorine. A colony of bats depicts the unselective gas‐phase radical‐chain mechanism with bromine. An angel views the selectivity control on earth.